A Microbiome-Based Solution to Address Alarming Levels of Drug-Resistant Bacteria in the Newborn Infant Gut. (October 2020) - Casaburi, Giorgio; Duar, Rebbeca; Henrick, Bethany; Frese, Steven
Abstract : Background: Recent studies have focused on the early infant gut microbiome, indicating that antibiotic resistance genes (ARGs) can be acquired in early life and may have long-term sequelae. Limiting the spread of antimicrobial resistance without triggering the development of additional resistance mechanisms would be of immense clinical value. Here, we present 2 analyses that highlight the abundance of ARGs in preterm and term infants and a proof of concept for modulating the microbiome to promote early stabilization and reduction in ARGs in term infants. Methods: Large-scale metagenomic analysis was performed on 2, 141 microbiome samples (90% from pre-term infants) from 10 countries; most were from the United States (87%) and were obtained from the Comprehensive Antibiotic Resistance Database (CARD). We assessed the abundance and specific types of ARGs present. In the second study, healthy, breastfed infants were fed B. infantis EVC001 for 3 weeks starting at postnatal day 7. Stool samples were collected at day 21 and were processed utilizing shotgun metagenomics. Selected antimicrobial-resistant bacterial species were isolated, sequenced, and tested for minimal inhibitory concentrations to clinically relevant antibiotics. Results: In the first study, globally, 417 distinct ARGs were identified. The most abundant gene among all samples was annotated as msrE, a plasmid gene known to confer resistance to macrolide-lincosamide-streptogramin B (MLSB) antibiotics. The remaining most-abundant ARGs were efflux-pump genes associated with multidrug resistance. No significant association in antimicrobial resistance was found when considering delivery mode or antibiotic treatment in the first month of life. In the second study, the EVC001-fed group showed a significant decrease (90%) in ARGs compared to controls ( P < .0001). ARGs that differed significantly between groups were predicted to confer resistance to β-lactams, fluoroquinolones, or multiple drug classes. Minimal inhibitory concentration assays confirmed resistance phenotypes among isolates Notably, we found resistance to extended-spectrum β-lactamases among healthy, vaginally delivered breastfed infants who had never been exposed to antibiotics. Conclusions: In this study, we show that the term and preterm infant microbiome contains alarming levels of ARGs associated with clinically relevant antibiotics harbored by bacteria commonly responsible for nosocomial infections. Colonization of the breastfed infant gut by a single strain of B. longum subsp infantis had profound impacts on the fecal metagenome, including reduction in ARGs and reduction of potential pathogens. These findings highlight the importance of developing novel approaches to limit the spread of ARGs among clinically relevant bacteria and the relevance of an additional approach in the effort to solve AR globally. Funding: Evolve BioSystems provided Funding: for this study. Disclosures: Giorgio Casaburi reports salary from Evolve BioSystems.